Personal values, motives, and healthy and sustainable food choices: Examining differences between home meals and restaurant meals - Claessens, I.W.H.; de Ridder, D.T.D.; Gillebaart, M. (Academic Press, 2023)
People are increasingly eating out in restaurants, where meals tend to be higher in calories, less nutritious, and contain more meat. In this paper, we argue that differences in the motivational processes underlying people’s food choices could help to explain why food choices made in restaurants are typically unhealthier and less sustainable than at home. Using online survey data from 301 Dutch participants, we compared the influence of stable personal values and transient food choice motives on the healthiness and sustainability of meals chosen in a hypothetical choice task, which was geared to the home and restaurant consumption contexts. As expected, participants opted for unhealthy and meat-based meals more often in the restaurant than the home context. Conservation values related negatively and self-transcendence values positively to choosing sustainable meals both in the home and in the restaurant context, although the relation with self-transcendence values was significantly weaker in the restaurant context. Also, taste and social eating were considered more important for choosing restaurant meals, while health was a more important motive for food choices at home. Finally, model comparisons revealed that motives were better predictors of healthy meal choices in both contexts, while the influence of values and motives on sustainable meal choices was more similar. In conclusion, the results from the present study enhance our understanding of differences between choosing home and restaurant meals by providing an account of the values and motives associated with the healthiness and sustainability of home and restaurant meal choices.
Keywords: Food choice motives; Food consumption context; Healthy eating; Personal values; Sustainable eating; General Psychology; Nutrition and Dietetics